The printed magazines ‘Education’ and the (re) work orientation of the pedagogical practices. Histories linked between São Paulo and Bogotá, 1932-1939 - Díaz Soler, Carlos Jilmar (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2013)
This article is part of a research is framed under a wider research aspect that seeks for the understanding of the production and circulation systems of pedagogic ideas, it takes as an essential part for it two magazines destined for the teachers’ development. Both entitled de Educação and Education, and published to the public teaching networks of São Paulo (Brazil) and Bogotá (Colombia), between the years 1932 and 1939, during this period these were supported by the respective States and they are organized by jointed groups to educational policies articulated, and they were in a process of (re)organization of teaching practices, and in the culture in general aspects, through the spread of its contents.